HUBUNGAN FAKTOR-FAKTOR PREDISPOSISI DENGAN KEPESERTAAN MANDIRI PROGRAM JAMINAN KESEHATAN NASIONAL DI BPJS KESEHATAN KANTOR KAB. LUMAJANG CABANG JEMBER - Ryan Arfiansyah; Asih Media Yuniarti (MEDICA MAJAPAHIT, 2024)
Having a health insurance in the global era is considered quite important The phenomenon that occurs in the field is the lack of public knowledge of the JKN Program managed by BPJS Kesehatan. The effort made is to optimize the National Health Insurance program. The purpose of this study was to analyze the relationship between predisposing factors and independent participation in the National Health Insurance Program at the BPJS Kesehatan Lumajang District Office Jember Branch. This study used correlational analytics with a cross-sectional approach, the population mounted to 51 participants, the sample obtained 34 participants. Data collected through questionnaires were analyzed using the Chi-Square test. The results showed that most had poor knowledge (44.1%), most had received information (61.8%), some had never had experience (64.7%), and most had unregistered status (58.8%). Based on the results of the study, there is a relationship between predisposing factors and Independent Participation in the National Health Insurance Program at BPJS Kesehatan Lumajang District Office Jember Branch. It is hoped that there will be innovations for BPJS Health regarding the ease of registration of BPJS Health participants and strategies are needed in the promotion of JKN so that the BPJS Health membership target can be achieved properly.